ELECTRONIC IDENTITY CARD FOR LAND JUSTICE: LEGAL POLICY ON THE IMPLEMENTATION OF ABSENTEE BASED ON ISLAM AND PANCASILA VALUES - Pratiwi, Irda; Bahmid, Bahmid (Proceeding International Seminar of Islamic Studies, 2024)
The research was motivated by the government's failure to finalize ownership of agricultural land in absentia. Pancasila as a guide to the value of justice should be used as government legal politics in carrying out preventive and repressive actions in synergy with the use of Information technology, which currently continues to grow. The Indonesian population, which is the majority of Muslims, certainly intersects between ideological, religious, and national ideologies. This research does not find new theories but wants to identify and examine how the perspective of Indonesian society in energizing religious ideology and Pancasila values which are believed by the Indonesian people as the basic foundation of national and state life. This research offers solutions for the use of E-KTP and data synergy between authorized institutions as an effort to prevent the absence of land ownership in terms of the perspective of Islamic legal values and Pancasila ideology. This research was conducted using normative research methods with a legal approach and legal doctrine.